2011
DOI: 10.1111/j.1398-9995.2010.02518.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE-sensitization to the cough suppressant pholcodine and the effects of its withdrawal from the Norwegian market

Abstract: Withdrawing of PHO lowered significantly within 1-2 years levels of IgE and IgE antibodies to PHO, MOR and SUX, and, within 3 years, the frequency of NMBA suspected anaphylaxis. The results strengthen the PHO hypothesis considerably and equally the need to question the existence of cough depressants containing PHO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 18 publications
0
44
0
4
Order By: Relevance
“…It has been suggested that pholcodine may sensitize and boost already sensitized individuals to synthesize sIgE antibodies to epitopes like tertiary and quaternary ammonium ions that are implicated in anaphylaxis from NMBA (3,4). Moreover, although the absence of firm evidence for clinical relevance of these sIgE antibodies this observation has already led to withdrawal and restrictive prescription of cough suppressant in some European countries (9). Our data demonstrate that patients with established pholcodine allergy might indeed show IgE-seroreactivity to NMBA such as rocuronium and suxamethonium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that pholcodine may sensitize and boost already sensitized individuals to synthesize sIgE antibodies to epitopes like tertiary and quaternary ammonium ions that are implicated in anaphylaxis from NMBA (3,4). Moreover, although the absence of firm evidence for clinical relevance of these sIgE antibodies this observation has already led to withdrawal and restrictive prescription of cough suppressant in some European countries (9). Our data demonstrate that patients with established pholcodine allergy might indeed show IgE-seroreactivity to NMBA such as rocuronium and suxamethonium.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism(s) for such a selective sensitization through pholcodine, that structurally differs only from morphine and pholcodine by its morpholinyl-ethyl-3 group at position 3, remain(s) obscure (1,7,8). Alternatively, although the clinical significance of these sIgE antibodies to NMBA remains entirely undetermined and controversial, it led to the withdrawal of the antitussive in Norway (March 2007) (9).…”
mentioning
confidence: 99%
“…Die für die Sensibilisierung verantwortlichen Substanzen haben bis auf die NH4 + -Verbindung zumeist keine chemische Verwandtschaft mit den Muskelrelaxanzien. Zu ihnen gehören haushaltsübliche Putzmittel, Zahnpasta, Haarund Hautpflegeprodukte, aber auch Medikamente [1,3,5,9,12]. Ein besonderes Beispiel ist Pholcodin, ein Morphinderivat, das in Norwegen als Inhaltsstoff eines Hustensafts verwandt wurde [5,6].…”
Section: Diskussionunclassified
“…Zu ihnen gehören haushaltsübliche Putzmittel, Zahnpasta, Haarund Hautpflegeprodukte, aber auch Medikamente [1,3,5,9,12]. Ein besonderes Beispiel ist Pholcodin, ein Morphinderivat, das in Norwegen als Inhaltsstoff eines Hustensafts verwandt wurde [5,6]. Offensichtlich kam es über die Sensibilisierung gegen die tertiäre Ammoniumstruktur von Pholcodin gehäuft zu kreuzallergischen Reaktionen auf Muskelrelaxanzien.…”
Section: Diskussionunclassified
See 1 more Smart Citation